Review of the genus Menestheus Stål, 1868 (Hemiptera: Heteroptera: Pentatomidae) - Faúndez, Eduardo I.; Rider, David A. (Zootaxa, 2018)
The Aeptini (Pentatomidae: Pentatominae) genus Menestheus Stål, 1868, is redescribed. The original misidentification of the type species for Menestheus is corrected by action of first reviser herein by establishing Paramenestheus nercivus non Dallas, 1851 sensu Stal (1868) = Menestheus cuneatus Distant, 1899 as the type species. Menestheus mcphersoni sp. nov. is described and illustrated. Characters separating the two species are discussed.